Functions of the bone morphogenetic protein signaling pathway through non-coding RNAs - Ural Mukhametov; Sergey Lyulin; Dmitry Borzunov; Galina Sufianova; Alina Shumadalova; Daming Zhang; Ilgiz Gareev (Non-coding RNA Research, 2022)
Bone morphogenetic proteins (BMPs) are proteins of the transforming growth factor-β (TGF-β) family, which plays an important role in the formation of skeletal and cartilage tissue and their regeneration. BMPs play a key role in the formation of new blood vessels and promote the migration, proliferation, and differentiation of mesenchymal stem cells (MSCs) into chondroblasts and osteoblasts. It is known that malfunction of BMPs signaling can cause a disease state. Epigenetic regulation of expression plays a key role in the control of many cellular processes. Important participants in this regulation are non-coding RNAs (ncRNAs), which are RNA molecules that are not translated into proteins. The best known of these are microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs). In addition, the results of many studies make it possible to establish an unambiguous functional relationship between these ncRNAs. Being involved in the regulation of a large number of target genes responsible for the life of the cell, miRNAs, lncRNAs, and circRNAs are essential for the normal development and functioning of the body, and the violation of their functions accompanies the development of many pathophysiological processes including oncogenesis. In the present review, we discuss different insights into the regulation of BMPs signaling pathway by miRNAs, lncRNAs and circRNAs governed.